Witkacy’s Amusia - Bocheński, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Witkacy suffered from amusia as a child and as an adult person. He was seriously interested in music only for a little over twenty years (1890–1914?). He wrote his main works as an amusic. The relation between amusia and metaphysical feelings may suggest that Witkacy wrote dramas and created painting compositions in order to evoke the lost strangeness of being. Amusia could have also been the reason for Witkacy’s ambiguity – he was defending and degrading high art at the same time.